Approval of unit rates of non-schedule item UPVC pipe changed from PVC pipe for conduit works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of unit rates of non-schedule item UPVC Pipe changed from PVC pipe for conduit works of Brac University new campus project.